Sport Tourism and its Subtypes, Benefits of Expanding Sport Tourism - Toychievna, Alieva Maxbuba; Izzatov, Bekhruz (European Journal of Life Safety and Stability (2660-9630), 2022)
Sport tourism is booming year by year all over the world. Most countries are taking a risk to invest millions of dollars to develop tourism. Especially, sport tourism is being regarded as one of the key features to develop the economy of a country. We can see this as an example of Qatar, the country that is trying to boost the development of sport tourism by creating new infrastructure of sport tourism by 2022 in order to hold FIFA World Cup. This article includes the up to date information that is going to explain the term of sport tourism and its types. While gathering the adequate information, I have searched and utilized the works of well-known scholars, teachers and journalists in the field of tourism, especially in sport tourism. Among them, I can show Valeriya Radomskaya, who is the professor of James Cook University. I would like to say thanks to all scholars for their handful articles and hope that this article will also be useful for the students and amateurs in the field of tourism.